Upaya Meningkatkan Ketahanan Keluarga dan Pelestarian Lingkungan Melalui Penanaman Tanaman Pangan Keluarga - Oktaviani, Maya; Elmanora; Kabbaro, Hurriyyatun; Rakhmawati, Tri Anggun; Rahmadina, Annisa Dwi; Nafisah, Nada (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
In the Jakarta area, the extensive replacement of green lands with concrete buildings have restricted the opportunity for family land ownership dedicated to conservation. This community service aims to develop motivation and a culture of planting to increase the knowledge, awareness, willingness, and ability of Family Welfare Empowerment (FWE) cadres and preschool teachers to preserve a culture of love for the environment and support family food security. The participants in this community service activity are FWE cadres and preschool teachers from the Jatinegara Kaum village. Conducted in August 2022 at the Child-friendly Integrated Public Space in Jatinegara Kaum, the project utilized the Participatory Action Research (PAR) method. Through descriptive analysis of the discussions, it was found that FWE cadres and preschool teachers actively engaged and showed their capability as pivotal agents in strengthening community resilience. This successful engagement underlines the potential for ongoing collaborative activities in community education and sustained support for the FWE cadres and preschool teachers.